Study on green infrastructure and sustainable urban development - Bedin, Érika Pena; Faria, Luiz Carlos de (Technical and Scientific Journal Green Cities, 2021)
In recent years, rapid urbanization and high-density construction have led to significant changes in hydrology and ecosystems in cities. As an opposite approach, green infrastructure has been suggested as an alternative strategy to mitigate the long-term impacts of urbanization and climate change. This study aimed to explore how the topic has been addressed in the scientific literature over the years. For that, a combination of systematic literature review and bibliometric analysis was performed to survey the articles; and Cluster Analysis and Principal Component Analysis (ACP) for treatment and validation of results. The results of this study indicate that the theme started in 2006 with its first publication and is in an emerging period since the year 2014 and 174 articles were identified representing 15 years of research. The conclusions indicate that although studies on the topic have increased significantly, the research showed the absence of reference articles involving actions that integrate the themes in a practical and generalizable way. Still, this research presents a broad reading of the literature and finds trends consistently reported by statistical methods. KEYWORDS: Green Infrastructure; Urban Sustainability; Urban Planning; Sustainable Development Goals (SDG).